Perfil dos pacientes revascularizados do miocárdio no período de 2004 a 2008 em um hospital universitário do Espírito Santo - Silva, Rita Inês Casagrande da (2009)
Objectives: to describe the profile of patients undergoing myocardial revascularization surgery (MRS), to describe the clinical profile and the intrahospital and extrahospital flow in perioperative of these patients. Method: It was carried out an analytical descriptive study using secondary data analysis of 147 records of patients submitted to MRS at a teaching hospital, Vitória, Espírito Santo, Brazil, from 2004 to 2008. It was performed a descriptive data analysis. Results: Statistically results demonstrate as the profile of higher incidence of MRS, males aged 50 to 69 years. Most patients had one or two associated diseases. Death occurred in 11.6%. The intrahospital flow presented a median waiting time between cardiac catheterization (Cath) and MRS of 55 days. There was suspension of the procedure for issues related to hospital structure and administration and related to the patient. The most common structural issue was the lack of beds in Intensive Care Unit (ICU). Conclusion: The analysis of the proposed clinical variables pointed to results consistent with the national scene in this area. However, in trajectory aspect, it was identified the influence of issues related to human resources management and structure for the development of hospital activities resulting in difficulty in attending demand for service capacity as well as the fragmentation of activities related to planning care, records and organization of medical records. With this study it was possible to construct a form for data collection in MRS which offers subsidies for the establishment of a database constructed by the author and to the implementation of interdisciplinary actions in cardiac surgical service.